-7(r+7)-3(+7r)=-30

Simple and best practice solution for -7(r+7)-3(+7r)=-30 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(r+7)-3(+7r)=-30 equation:



-7(r+7)-3(+7r)=-30
We move all terms to the left:
-7(r+7)-3(+7r)-(-30)=0
We add all the numbers together, and all the variables
-7(r+7)-3(+7r)+30=0
We multiply parentheses
-7r-21r-49+30=0
We add all the numbers together, and all the variables
-28r-19=0
We move all terms containing r to the left, all other terms to the right
-28r=19
r=19/-28
r=-19/28

See similar equations:

| 0.5x+4=2x | | 3/2t+1=2/t-2 | | 7+√(x-1)=2 | | 24x+6=-12 | | 24x-6=-12 | | 8d/8=72/2 | | 8n-3=22 | | 2(x-7)+2(3x-8)=2 | | 0.5x+2=2x+-2 | | 8n−3=22 | | x3–9x2–36x=0 | | x+3=-2x+24 | | 2+5x+4x+7=90 | | 8(n+1)+3(8n-2)=2 | | 5x-4=16-10x/3 | | 2x^2-x-30=123 | | ×+23+4x+17+80=180 | | 1-3c=6 | | 612-7y=-9 | | 5x-13+4=180 | | 2k^+9k=-7 | | 12.r=144 | | 11.18+n=22.18 | | 7.5n=82.5 | | 3/4n=81/4 | | -26=-8(n+8)+2(-6n-1)-26 | | 3708=36(p+25) | | 25=5(2-n)-2(-3+2n)25 | | (-x)12=45 | | 0.07x+0.03=0.1 | | -3(1-4x)+7(-3x-5)=-20 | | x7=3x+5 |

Equations solver categories